Indigenous law, colonial injustice and the jurisprudence of hybridity. Issue 1 (2nd January 2018) - Nursoo, Ida
ABSTRACT: As Aboriginal and Torres Strait Islander peoples have increasingly come into contact with the mainstream Australian legal system, as offenders, litigants or victims of it, that system has not only had to confront its legacy of colonial violence, but it has been called to question first, the legitimacy of its own authority based upon that violence and, second, the limits of its ability to properly administer justice for First Nations Australians. This paper will address the question of "what does it mean to decolonise justice for First Nations Australians?" It argues that decolonising justice entails nurturing a "jurisprudence of hybridity" as a response to the imbalance whereupon colonial justice violated Indigenous Law. This process, the paper argues, entails three steps: decolonising the mind, listening and learning of Indigenous Law ways; destabilising colonial legal authority in order to examine its knowledge/power relations and shifting the paradigm of legal pluralism from monist-pluralism to pluralist-pluralism.